Pengaruh Komunikasi Efektif Untuk Meningkatkan Hasil Belajar Mahasiswa - Hugo Aries Suprapto (Universitas Muhammadiyah Purwokerto, 2018)
Abstract With effective communication, the managerial functions that originated from the functions, implementation and monitoring can be achieved. This study used an experimental method. Subjects were students of the seventh semester of Industrial Engineering as many as 25. There is a significant influence effective communication to increase student learning outcomes. The data was processed with SPSS 22. The results showed, normality test, homogeneity and T Samples Paired with a significant level of α = 5%, the normality test results obtained prior to the effective communication Kolmogorof-Smirnov value Sig. 0190, and Shapiro-Wilk 0215 so that at α = 5% = 0:05 <Sig. = 0, the sample data came from a normal distribution. While the test results of normality after the effective communication of values obtained Kolmogorof-Smirnov Sig. 0134, and Shapiro-Wilk 0346 so that at α = 5% = 0:05 <Sig. = 0, the sample data came from a normal distribution. At Variance Homogeneity Test Levene Value Sig. 0096, at a significance level of α = 5% = 0:05 <Sig.0.096 so that it can be said of data samples derived from the variances are homogenous, it can be concluded on a confidence level of 95%, on average after the effective communication to improve student results mean for entrepreneurship courses 80.9600) compared to before using effective communication (mean of 64.7200), rose by 16:24. In other words, the use of effective communication wear a significant effect on improving learning outcomes 95%. This study gives suggestions to overcome the problems found in the study. Keywords: effective communication, learning outcomes